2019
DOI: 10.1371/journal.pntd.0007602
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β inhibitor therapy decreases fibrosis and stimulates cardiac improvement in a pre-clinical study of chronic Chagas’ heart disease

Abstract: TGF-β involvement in Chagas disease cardiomyopathy has been clearly demonstrated. The TGF-β signaling pathway is activated in the cardiac tissue of chronic phase patients and is associated with an increase in extracellular matrix protein expression. The aim of this study was to investigate the effect of GW788388, a selective inhibitor of TβR1/ALK5, on cardiac function in an experimental model of chronic Chagas’ heart disease. To this end, C57BL/6 mice were infected with Trypanosoma cruzi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 60 publications
8
68
0
3
Order By: Relevance
“…Moreover, we found that the reduced expression of pro-inflammatory cytokines and TGF-β was associated with heart function amelioration. Similarly, a reduction in serum TGF-β concentration through pharmacological treatment associated with heart function improvement has been observed by others ( 71 ).…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, we found that the reduced expression of pro-inflammatory cytokines and TGF-β was associated with heart function amelioration. Similarly, a reduction in serum TGF-β concentration through pharmacological treatment associated with heart function improvement has been observed by others ( 71 ).…”
Section: Discussionsupporting
confidence: 69%
“…We have previously shown that chronically Colombianinfected C57BL/6 mice show cardiomegaly, echocardiographic and electrical abnormalities that resembles those found in Chagas' heart disease (6,26,32,46). These features were associated with the intensity of myocarditis and levels of proinflammatory cytokines in the heart tissue (26,30).…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, we did not observe significant differences between the losartan and control groups in LP-PRP or WB TGF-β1 concentrations. TGF-β1 is an essential Smad factor involved in downstream intracellular signaling and, more specifically, increasing ECM protein expression (i.e., matrix metalloproteinases [MMPs], tissue inhibitors of metalloproteinases [TIMPs]) [ 38 ]. The most notable role of TGF-β1 is stimulating fibrosis formation during connective tissue remodeling [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, several anti-fibrotic medications have been developed to reduce local and systemic TGF-β1 levels by implicating the Smad2/3 pathway. Angiotensin-receptor blocker, losartan, has demonstrated its anti-fibrotic effects in cardiac [ 8 , 38 , 40 , 41 , 42 ] and skeletal muscle [ 12 , 13 , 14 , 15 , 19 ], as well as reducing systemic levels of TGF-β1 in transplant patients [ 43 , 44 ]. In the present study, there were no significant differences between TGF-β1 levels in the losartan and control groups; however, losartan dosing and timing in which the blood specimens were collected could have had an impact on TGF-β1 expression.…”
Section: Discussionmentioning
confidence: 99%